Globalization and liberalization : effects of international economic relations on poverty : inter-agency thematic contribution to the International Year for the Eradication of Poverty - United Nations Conference on Trade and Development (New York ; Geneva : UNCTAD, 1996)
Papers presented at an inter-agency seminar held April 15-17, 1996, in Geneva, Switzerland.
Papers presented at an inter-agency seminar held April 15-17, 1996, in Geneva, Switzerland.
Includes bibliographical references.
oif 22/07/16
Loans
Keywords: International economic relations; Poverty